2019
DOI: 10.1590/s1980-6574201900030003
|View full text |Cite
|
Sign up to set email alerts
|

Association between insufficient level of physical activity and multiple health risk behaviors in adolescents

Abstract: To verify the association between insufficient level of physical activity and multiple health risk behaviors (HRB) in adolescents. Methods: This is an epidemiological study with cross-sectional design carried out in 2016 with 3,617 adolescents aged 14-19 years and enrolled in the public-school system of Sergipe, northeast Brazil. Data were collected using the Global School-based Student Health Survey (GSHS/WHO). The insufficient level of physical activity was defined as not achieving at least 60 minutes of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
1
2
0
1
Order By: Relevance
“…When considering race and financial difficulty as proxies for socioeconomic status, the present study confirms the influence of socioeconomic level on the practice of PA 44,45 . Adolescents who declared themselves to be black and who had financial difficulties during the pandemic had a higher incidence of insufficient PA.…”
Section: Discussionsupporting
confidence: 76%
“…When considering race and financial difficulty as proxies for socioeconomic status, the present study confirms the influence of socioeconomic level on the practice of PA 44,45 . Adolescents who declared themselves to be black and who had financial difficulties during the pandemic had a higher incidence of insufficient PA.…”
Section: Discussionsupporting
confidence: 76%
“…Ao considerarmos raça e dificuldade financeira como proxies de condição socioeconômica, o presente estudo confirma a influência do nível socioeconômico na prática de AF 44,45 . Os adolescentes que se autodeclararam da raça/cor da pele preta e que apresentaram dificuldades financeiras durante a pandemia apresentaram maior incidência de AF insuficiente.…”
Section: Resultsunclassified
“…The questionnaire used was a Portuguese version of the Global School-Based Student Health Survey (GSHS/WHO) [21], already used in previous studies [16]. Data was collected by researchers with a degree in physical education, previously trained to questionnaire application.…”
Section: Design and Samplementioning
confidence: 99%
“…In Brazil, environmental characteristics such as lack of bike path and heavy traffic, have stood out as barriers to the adoption of bicycle use in adults [15]. In Sergipe, a state in Northeast Brazil, only 16.7% of the adolescents meet the overall health recommendations of PA (it is suggested that adolescents should accumulate at least 60 minutes of moderate-to-vigorous PA daily) [16], but the prevalence of Inactive Commuting (INAC) of these adolescents is still unknown. Therefore, it is necessary to focus attention on other domains of PA, especially the commuting to school, given its positive association with health benefits [17].…”
Section: Introductionmentioning
confidence: 99%